Incidence and predation rate of hornet (Vespa spp.) on European honeybee (Apis mellifera L.) apiary at mid-hill areas of Lalitpur district, Nepal - Bista, Sanjaya; Thapa, Resham B.; K.C., Gopal Bahadur; Pradhan, Shree Baba; Ghimire, Yuga Nath; Aryal, Sunil (Journal of Agriculture and Natural Resources, 2020)
Predatory hornets are considered as one of the major constraints to beekeeping industry. Therefore, its incidence and predation rate was studied throughout the year at two locations- rural and forest areas of mid-hill in Laliptur district during 2016/017 to 2017/018. Observation was made on the number of hornet and honey bee captured by hornet in three different times of the day for three continuous minutes every fortnightly on five honeybee colonies. During the study period, major hornet species captured around the honeybee apiary at both locations were, Vespa velutina Lepeletier, Vespa basalis Smith, Vespa tropica (Linnaeus) and Vespa mandarina Smith. The hornet incidence varied significantly between the years and locations along with different observation dates. Their incidence and predation rates were low in early spring and summer that gradually increased with the highest peak in October and November in both locations. The maximum predation was on mid-November (62.07%) and early-November (53.49%) at rural and forest locations, respectively during 2016/017. In 2017/018, the highest predation was on early-November (70.27%) at rural area while it was in mid-November (58.62%) in the apiaries near the forest area. The population of hornet was considerably higher at forest areas and their incidence around the honeybee apiaries were negatively correlated with rainfall. Hence, assessment of the temporal and spatial population variations and predation rates along with weather parameters is helpful in to develop sustainable management plans of the hornet in apiary.